2021
DOI: 10.1002/jmri.27938
|View full text |Cite
|
Sign up to set email alerts
|

A General Model to Calculate the Spin–Lattice Relaxation Rate (R1) of Blood, Accounting for Hematocrit, Oxygen Saturation, Oxygen Partial Pressure, and Magnetic Field Strength Under Hyperoxic Conditions

Abstract: Background: Under normal physiological conditions, the spin-lattice relaxation rate (R1) in blood is influenced by many factors, including hematocrit, field strength, and the paramagnetic effects of deoxyhemoglobin and dissolved oxygen. In addition, techniques such as oxygen-enhanced magnetic resonance imaging (MRI) require high fractions of inspired oxygen to induce hyperoxia, which complicates the R1 signal further. A quantitative model relating total blood oxygen content to R1 could help explain these effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Finally, this model does not represent the r 1Ox in blood and tissues, where the addition of proteins, lipids, and deoxyhemoglobin will affect the R 1 -pO 2 relationship; however, we have created a separate general model to calculate the R 1 of blood, accounting for hematocrit, oxygen saturation, oxygen partial pressure, and magnetic field strength under hyperoxic conditions. 46 For convenience, however, we have listed the reported literature values found in tissue and blood in Supplementary Table S4-nine values from blood and three from tissues. For the purpose of this model, only the 28 r 1Ox values in water, saline, vitreous fluid, and plasma were used.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, this model does not represent the r 1Ox in blood and tissues, where the addition of proteins, lipids, and deoxyhemoglobin will affect the R 1 -pO 2 relationship; however, we have created a separate general model to calculate the R 1 of blood, accounting for hematocrit, oxygen saturation, oxygen partial pressure, and magnetic field strength under hyperoxic conditions. 46 For convenience, however, we have listed the reported literature values found in tissue and blood in Supplementary Table S4-nine values from blood and three from tissues. For the purpose of this model, only the 28 r 1Ox values in water, saline, vitreous fluid, and plasma were used.…”
Section: Limitationsmentioning
confidence: 99%
“…It is known that the values estimated by the r1 Ox model and R1 Blood models by Bluemke et al 15,19 both agree well with empirical measurements (R 2 = 0.93 and 0.93); however, since the tissue compartment of this model contains variables that were not measured at the time of OE-MRI data collection (i.e., hematocrit, changes in arterial PO 2 , tumor blood volume), it is not possible to quantitatively compare the model ΔR1 predictions to the measured ΔR1 with metrics such as R 2 and MSE. Instead, we used a variety of reported ΔR1 from OE-MRI literature to gain a rough estimation of the accuracy of this model: qualitative ΔR1 responses, categorized by different tumor tissue types by the authors of the OE-MRI literature, are listed in Supporting Information Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…The ΔR1 induced from supplemental oxygen in the arterial (ΔR1 B,A ) and venous (ΔR1 B,V ) blood compartments can both be calculated from the following equation ΔR1Bgoodbreak=R1b()PO2,italicoxgoodbreak−R1b()PO2,italicair$$ \Delta R{1}_B=R{1}_b\left(P{O}_{2, ox}\right)-R{1}_b\left(P{O}_{2, air}\right) $$ where R1 b (PO 2 ) is the general equation for calculating the R1 of blood by Bluemke et al 19 (shown in Figure 3): R1bPO2=feR1italiceox+r1italicdHbfalse[italicHbfalse]1PO2nPO2n+P50n+1feR1p+r1italicpOxPO2$$ {\displaystyle \begin{array}{cc}R{1}_b\left(P{O}_2\right)& ={f}_e\left(R{1}_{eox}+r{1}_{dHb}\left[ Hb\right]\left(1-\frac{P{O_2}^n}{P{O_2}^n+P{50}^n}\right)\right)\\ {}& \kern1em +\left(1-{f}_e\right)\left(R{1}_p+r{1}_{pOx}P{O}_2\right)\end{array}} $$ where R1 b is the relaxation rate of whole blood, R1 eox is the relaxation rate of erythrocytes when SO 2 = 100%, [Hb] is the mean corpuscular hemoglobin concentration (5.15 mmol Hb tetramer/L plasma), r1 dHb is the molar relaxivity of deoxyhemoglobin (in s −1 L plasma in erythrocyte/mmol Hb tetramer), n is the Hill exponent for hemoglobin (typically 2.7), 30 R1 p is the longitudinal relaxation rate of plasma (s −1 ), and r1 pOx is the relaxivity of dissolved oxygen in the plasma in s −1 mmHg −1 oxygen. The variable f e is the fraction of water in whole blood that resides in erythrocytes (0–1), which is described by the equation: fe(Hct…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations